Hemodynamic effects of volume replacement with saline solution and hypertonic hydroxyethyl starch in dogs - Udelsmann,Artur (2009)
PURPOSE: To investigate hemodynamic response to volume replacement with saline solution and hypertonic hydroxyethyl starch in hypovolemic dogs. METHODS: Forty dogs under general anesthesia and hemodynamic monitoring, following measurements at baseline, were bled 20 ml.Kg-1 and parameters were measured again after 10 minutes. The animals were randomly divided in two groups and volume replacement was performed with saline solution twice the volume removed or 4 ml.Kg-1 of hypertonic hydroxyethyl starch. Hemodynamic data were again measured after 5, 15, 30, 45 and 60 minutes. RESULTS: With both solutions values returned to satisfactory hemodynamic levels. With saline solution, there was a greater amplitude in variations that tended to decrease progressively. With hypertonic hydroxyethyl starch, the parameters studied returned more rapidly to levels similar to those at baseline and varied less. CONCLUSION: Both solutions proved to be efficient at replacing volume in the short period studied, although hypertonic hydroxyethyl starch produced more stable results.